Aplication Development and It’s Aplicated in Yasmin Store of Buton Sentral Distric - La Sudarman; La Jejen; Poniasih Lelawatty; Muhammad Tasjiddin Teheni; Murni Sari; Sarimuddin Sarimuddin; Wa Ode Fera Azriani (Jurnal Pengabdian Masyarakat Borneo, 2022)
The increasingly rapid development of technology has a real impact on changes in various sectors, not least in the marketing sector, especially in the recording of business transactions. Based on the results of initial field observations, it was found that the Yasmin Store still uses manual recording, this is what underlies the implementation of abdimas activities in the form of developing a sales information system application and its application to the Yasmin Store so that this application can provide real benefits in terms of recording business transactions. Sales information system application designed in the form of a flow chart and user interface program design so as to form a complete system component that is incorporated in the sales application according to user needs. The program interface design is made user friendly so that user actors can easily operate the application. Methods of implementing activities include: 1) Needs analysis; 2) Application design; 3) Feasibility test; 4) Testing/Implementation; 5) Application of sales information system application; 6) Evaluation and 7) Reporting on the results of activities. The benefits of using this application include making it easier for users to check: 1) stock of goods on a regular basis; 2) customer data reports 3) supplier data reports and check sales and purchase recapitulation reports per day, month, or year. The final result expected in this activity is that the user is able to operate and use the sales information system application permanently.